Covid-19 – Impacts on Society and Economy - Carl Heinz Daube (ZBW - Leibniz Information Centre for Economics, 2022)
Since the turn of the year 2019/2020, Covid-19 has determined large parts of public and private life worldwide. The restrictions are causing social and economic issues in all areas of life. This working paper attempts to quantify and qualify some impacts on our society and our economy and to analyse in more detail some of the effects. – – Covid-19 bestimmt seit dem Jahreswechsel 2019/2020 weltweit weite Teile des öffentlichen und privaten Lebens. Die Einschränkungen in vielen Lebensbereichen können nicht ohne gesellschaftliche und ökonomische Folgen bleiben. In diesem Working-Paper wird versucht, einige Auswirkungen auf unsere Gesellschaft und unsere Wirtschaft qualitativ und quantitativ zu erfassen und näher zu analysieren.
Keywords: G10; 330; Covid-19; impacts on economy; impacts on society; impacts on financial markets